If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -864 = 652 Reorder the terms: -864 + y = 652 Solving -864 + y = 652 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '864' to each side of the equation. -864 + 864 + y = 652 + 864 Combine like terms: -864 + 864 = 0 0 + y = 652 + 864 y = 652 + 864 Combine like terms: 652 + 864 = 1516 y = 1516 Simplifying y = 1516
| 0.5a+8.75=13.25 | | (y-4)-(y+3)=9y | | 0.5a+8.75=13.24 | | 3x+15=3x+5 | | -16x^2+25x+3=0 | | -3(2+n)-(5-3n)=1 | | 5(n+4)+9n=(5n+20)+9n | | 11(x+5)=10(x+5) | | F-7=84 | | -5t(t-1)+8t=7t-2 | | 4n+7=-53 | | x(x)-24x+100=0 | | 10.6y-3=0.71 | | 110=x+25 | | 7.7j=76 | | 8y=2x+5 | | 35x^2+15x=0 | | 4n-7=-53 | | 4In(x+5)-5Inx= | | 2x+(-5x)-24=4x+11-(-28) | | 7-w=21.7 | | -234=m-94 | | 2a=-a+9 | | 7y-2+5y-6= | | 14n+4=14n+20 | | (500-4)*A=144 | | 14x=9x+60 | | 8(x-2)-5(x-4)=20+x | | 2x(3)+x(2)=7 | | 20x-5=7+16x | | 8(4x+6)+6x= | | -14=5-8 |